Arbuscular Mycorrhizal Colonization in Five Tropical Forest Tree Legumes of Chittagong University Campus in Bangladesh - Nure Ferdousee,; Khaled Misbahuzzaman ,; A.T.M. Rafiqul Hoque, (Journal of Basic & Applied Sciences, 2021)
Arbuscular mycorrhizal (AM) colonization in five tropical forest tree legumes (Gliricidia sepium, Dalbergia sissoo, Indigofera tysmanii, Delonix regia and Samanea saman) was investigated in Chittagong University (CU) campus. The results of the present study clearly suggests that, Vesicular AM fungi (VAM) are common in all the studied forest tree species, and that the studied forest tree species differ in their rates of AM formation. The intensity of colonization is maximum (98%) in I. tysmonii followed by D. sissoo (95%), D. regia (63%), S. saman (59%) and G. sepium (52%). Coiled structures of hyphae were recorded in D. regia. Arbuscule formation was recorded in D. sissooand in I. tysmonii. Mycorrhizal spores were found in rhizosphere soils of all the sites. Glomus, Acaulospora, Entrophospora and Gigaspora spores were identified in all the hosts. Forest plants differ in their rates of AM formation. Edhapic conditions like moisture content, soil pH also influence the extent of root colonization. Keyword: Mycorrhizae, Legume, Colonization, Edhapic condition, Rhizosphere, Underground networking.